CFD Study Based on Effect of Employing the Single-Walled Carbon Nanotube (SWCNT) and Graphene Quantum Dots (GQD) Nanoparticles and a Particular Fin Configuration on the Thermal Performance in the Shell and Tube Heat Exchanger - Rostami, Mohammadreza Hasandust; Najafi, Gholamhassan; Ghobadian, Barat; Motevali, Ali; Che Sidik, Nor Azwadi (CFD Letters, 2020)
In this research, the thermal attributes of shell and finned tube heat exchanger such as thermal efficiency, pressure drop, heat transfer rate and average temperature in the tube side of heat exchanger with using the different volume concentration of nanoparticles (SWCNT and Graphene quantum dot) at the various Reynolds number by applying either fin blades and without fin blades have been conducted numerically. In this heat exchanger the hot fluid or nanofluid flows in the tube section and cold fluid or pure water moves in the shell side. As regarding to results obtained the majority of thermal characteristics like heat transfer rate, pressure drop and effectiveness enhanced with augmentation of Reynolds number and increasing of volume concentration of nanofluids to 1% volumetric of working fluid whereas at the higher volume concentrations of nanoparticles (upper from 1% volumetric) the thermal properties of heat exchanger decreased generally. Also pressure drop intensifies with increment of Reynolds number and volume concentration of nanoparticles that at higher Reynolds number the effects of nanoparticles on the pressure drop were more noticeable. The average temperature of heat exchanger in the end section of inside tubes increased with augmentation of Reynolds number and nanoparticles. Finally, according to the results obtained in this study, most impression on the thermal attributes enhancement was found by employing of finned tubes compared to other factor which this factor increased heat transfer rate of heat exchanger by almost 188% also the effects of nanoparticles at the high levels of volume concentration especially for 5% of SWCNT nanoparticle on the pressure drop obtained about 80% compared to the base fluid.